2022
DOI: 10.3389/fped.2022.919572
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sleep disorders and attention-deficit–hyperactivity disorder in children

Abstract: ObjectiveTo explore the correlation between sleep disorders and attention-deficit–hyperactivity disorder (ADHD) in children.MethodsWe studied 100 Chinese children (70 boys and 30 girls; mean age, 8.77 ± 2.39 years). Parents completed the Children's Sleep Disturbance Scale (SDSC) and the Swanson Nolan and Pelham Version IV Scale (SNAP-IV) questionnaires. SNAP-IV and SDSC scores were compared in children with and without sleep disorders and ADHD.ResultsThere were significant differences in SDSC scores, Arousal D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Many studies have reported an association between sleep problems and increased severity of ADHD symptoms or behavioral problems in school-aged children with ADHD. 6,7 For specific sleep problems in preschool children with ADHD, only a study by Stickley (2021) 8 found that the prevalence of sleep problems in these children was as high as 83.6%. The most common sleep problems in these children included awakening at night (59.6%), nightmares (29.9%), and snoring (22.6%).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported an association between sleep problems and increased severity of ADHD symptoms or behavioral problems in school-aged children with ADHD. 6,7 For specific sleep problems in preschool children with ADHD, only a study by Stickley (2021) 8 found that the prevalence of sleep problems in these children was as high as 83.6%. The most common sleep problems in these children included awakening at night (59.6%), nightmares (29.9%), and snoring (22.6%).…”
Section: Introductionmentioning
confidence: 99%
“…Noradrenergic and dopaminergic neurotransmitter pathways have been implicated in both ADHD and sleep disorders [ 6 ] and the nature of the relationship between them is considered bidirectional [ 7 ]. It has been noted that symptoms of ADHD, such as inattention, hyperactivity, and irritability, may mimic daytime symptoms of primary sleep disorders, and sleep disorders may exacerbate ADHD symptoms [ 8 ]. Thus, there exists the possibility that sleep disorders are misdiagnosed as ADHD and vice versa [ 9 ].…”
Section: Introductionmentioning
confidence: 99%